(untitled) (Islas, 2021)
This work is about the social mediations that impact in the institutional administration of the Programs of Cultural development in Villa Clara and its materialization in the current context of the cultural practices. The sociological treatment contribute to the clarifying the social determination of the matter, in the face of the multiplicity in the cultural ways. It also legitimize the cultural politics as a rule of their treatment in spaces of institutional encounter with the community environment and like road of hegemony construction and coherence in the Cuban social project.